2021
DOI: 10.3390/jcm10235686
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of Transbronchial Lung Cryobiopsy Compared to Transbronchial Forceps Biopsy in Patients with Sarcoidosis in a Prospective, Randomized, Multicentre Cross-Over Trial

Abstract: Background: Transbronchial lung forceps biopsy (TBLF) is of limited value for the diagnosis of interstitial lung disease (ILD). However, in cases with predominantly peribronchial pathology, such as sarcoidosis, TBLF is considered to be diagnostic in most cases. The present study examines whether transbronchial lung cryobiopsy (TBLC) is superior to TBLF in terms of diagnostic yield in cases of sarcoidosis. Methods: In this post hoc analysis of a prospective, randomized, controlled, multicentre study, 359 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
1
0
1
Order By: Relevance
“…This could explain the similar diagnostic yield of TBCB and TBFB in our study among patients with OP or EP. However, we did find TBCB to be superior for sarcoidosis (87% vs. 46%), as was shown in a recent prospective study by Hantschel et al [28]. TBCB and TBFB also showed similar results for patients with iNSIP.…”
Section: Discussionsupporting
confidence: 88%
“…This could explain the similar diagnostic yield of TBCB and TBFB in our study among patients with OP or EP. However, we did find TBCB to be superior for sarcoidosis (87% vs. 46%), as was shown in a recent prospective study by Hantschel et al [28]. TBCB and TBFB also showed similar results for patients with iNSIP.…”
Section: Discussionsupporting
confidence: 88%
“…Bei Sarkoidose liegt die diagnostische Wertigkeit der TBB ohne EBUS bei 71 %, mit EBUS steigt sie auf 87 % [55,129]. Ergebnisse einer prospektiven, randomisierten, multizentrischen Studie mit Cross-Over-Design (TBB vs. TBLC) wiesen eine deutlich niedrigere Trefferquote für die durch TBB als TBLC gewonnenen Proben auf (35 % vs. 59 %) [130]. Wegen der niedrigen Fallzahl (n = 17) müssen die Ergebnisse dieser Subgruppenanalyse allerdings mit Vorsicht interpretiert werden.…”
Section: Gewinnung Von Biopsiematerials In Der Diagnostik Der Ildunclassified
“…Considering the role of TBLB in the diagnosis of TB, Chan et al reported the highest sensitivity of TBLB (77% of sensitivity) when using radial probe endobronchial ultrasound guidance, whereas other studies also reported the sensitivity range of 16–77% for the diagnosis of TB by using TBLB alone ( 49 , 50 ). Transbronchial lung cryobiopsy (TBLC) which retrieves lung tissue by freezing probe via bronchoscopy is considered to provide better diagnostic yield than TBLB in interstitial lung diseases including sarcoidosis as described in recent studies ( 51 , 52 ). However, the risk of hemorrhage and pneumothorax, the main complications of TBLC, is extremely high, and its indication should be carefully considered.…”
Section: Diagnostic Approachmentioning
confidence: 99%